1999
DOI: 10.1128/jcm.37.1.146-151.1999
|View full text |Cite
|
Sign up to set email alerts
|

Novel Intestinal Helicobacter Species Isolated from Cotton-Top Tamarins ( Saguinus oedipus ) with Chronic Colitis

Abstract: A disease similar to ulcerative colitis in humans has been identified in cotton-top tamarins (CTTs) in captivity. The clinical signs include weight loss, diarrhea, and rectal bleeding with the pathological features and biochemical abnormalities of ulcerative colitis. Approximately 25 to 40% of these animals develop colon cancer after 2 to 5 years of captivity. An infectious etiology has been proposed; however, no microbial agent to date has been identified.Helicobacter spp. have been associated with enterocoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 89 publications
(39 citation statements)
references
References 32 publications
0
39
0
Order By: Relevance
“…The suggestion of an infectious aetiology for CTT which is a highly prevalent pancolitis in captive monkeys but rare in the wild dates back to the observations of Johnson et al [56]. A novel urease-negative Helicobacter species was identified from monkeys with this condition [57]. This organism, previously dubbed ''Flexispira taxon'', is now thought to incorporate at least 10 Helicobacter taxa, including Helicobacter bilis, Helicobacter callitrichis and Helicobacter trogontum, along with other species which have not been formally characterised but which are often referred to as Helicobacter rappini or Helicobacter flexispira [58].…”
Section: Helicobactermentioning
confidence: 94%
“…The suggestion of an infectious aetiology for CTT which is a highly prevalent pancolitis in captive monkeys but rare in the wild dates back to the observations of Johnson et al [56]. A novel urease-negative Helicobacter species was identified from monkeys with this condition [57]. This organism, previously dubbed ''Flexispira taxon'', is now thought to incorporate at least 10 Helicobacter taxa, including Helicobacter bilis, Helicobacter callitrichis and Helicobacter trogontum, along with other species which have not been formally characterised but which are often referred to as Helicobacter rappini or Helicobacter flexispira [58].…”
Section: Helicobactermentioning
confidence: 94%
“…Comparison of these sequences with over 100 Helicobacter sequences in our database indicated that the isolates represent a new Helicobacter species, for which we propose the name H. marmotae. The sequence for H. marmotae is most closely related to sequences from helicobacters isolated from rhesus monkeys (AF333339 on April 30, 2020 by guest http://jcm.asm.org/ and AF333340 [11]) and cotton-top tamarins (AF107494 [30]) and H. fennelliae. The H. marmotae sequence differs from these sequences by 4 to 5% (Fig.…”
Section: Whv Statusmentioning
confidence: 82%
“…The finding of IBD, sometimes in conjunction with colon adenocarcinoma or hepatobiliary inflammatory changes, is reminiscent of findings reported in other nonhuman primates (NHPs) infected with Helicobacter spp [64e68]. A novel Helicobacter sp., Helicobacter saguini, was identified in cotton-top tamarins diagnosed with progressive colitis mimicking features of ulcerative colitis in humans [63,69]. The diarrheic marmosets reflected only the clinical state of the animal at the time of sampling.…”
Section: Clinical Signsmentioning
confidence: 99%